Evaluation of Pharmacokinetics and Safety of the Biosimilar (B01711) and Insulin Degludec/Insulin Aspart (IDegAsp, Ryzodeg) in Healthy Chinese Adults in a Randomized, Open-Label, Single-Dose, Crossover, Phase I Study - Liu H; Cao H; Li T; Chen X; Yu H; Sun J; Yu Y (Drug Design, Development and Therapy)
Hui Liu,1,2 Haiyan Cao,3 Ting Li,4 Xinlei Chen,1 Hongling Yu,1 Jingfang Sun,3 Yerong Yu1 1Department of Endocrinology and Metabolism, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Clinical Trial Center, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Hui Sheng Bio-pharmaceutical Co., Ltd., Tonghua, Jilin, People’s Republic of China; 4Health Management Center, General Practice Medical Center, West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Yerong Yu, Department of Endocrinology and Metabolism, West China Hospital of Sichuan University, Guoxue Lane No. 37, Wuhou District, Chengdu, Sichuan, People’s Republic of China, Email yerongyu@scu.edu.cnObjective: B01711 is a biosimilar of insulin degludec/insulin aspart (IDegAsp 70/30). This randomized, open-label, single-dose, crossover, phase I study aimed to evaluate the pharmacokinetics (PK) and safety of B01711 compared to its original product (Ryzodeg) in healthy Chinese volunteers.Methods: The study was conducted between April and August 2022, this study included 32 participants (22 males and 10 females) who received subcutaneous injections of both B01711 and Ryzodeg, with a ≥ 14-day washout period between treatments. All participants completed the study without any dropouts. Blood samples were collected at pre-defined intervals for PK analysis.Results: The primary PK parameters included the area under the curve (AUC) of insulin degludec (IDeg) from 0 to 24 hours (AUCIDeg, 0– 24 h), AUC of insulin aspart (IAsp) from 0 to the time of the last measurable value (AUCIAsp, 0-t), and the peak concentration of IAsp (CIAsp, max). PK equivalence would be established if the 90% confidence intervals (CIs) of least squares (LS) mean ratios of log-transformed values of primary PK endpoints for B01711 compared with Ryzodeg fell within the range of 80.0% to 125.0%. Safety was monitored throughout the study. The LS-mean ratios and corresponding 90% CIs were 106.1% (101.9%, 110.5%) for AUCIDeg, 0– 24 h; 103.9% (100.2%, 107.6%) for AUCIAsp, 0-t; and 110.1% (101.0%, 119.9%) for CIAsp, max. Two treatment-emergent adverse events (TEAEs) were reported in two subjects (6.3%) in the B01711 group, and seven TEAEs were reported in seven subjects (21.9%) in the Ryzodeg group. The most common TEAE was a decrease in hemoglobin. The adverse events (AEs) of hypokalemia and hypoglycemia were identified as treatment-related AEs (TRAEs) and all TRAEs were mild.Conclusion: This study demonstrated the PK equivalence of the two drugs and confirmed that both were well-tolerated.Keywords: B01711, IDegAsp, pharmacokinetics, healthy subjects, Ryzodeg, phase I study